Potensi Rimpang Kencur (Kaempferia galanga Linn.) sebagai Agen Imunomodulator terhadap Performa Ayam Broiler (Gallus domesticus sp.): Potential of Galangal Rhizome (Kaempferia galanga Linn.) as an Immunomodulatory Agent for Broiler Chicken (Gallus domesticus sp.) Performance - Halisa; Hernawati (Life Science, 2025)
Broiler chickens (Gallus domesticus sp.) are one of the most sought-after commodities due to their high productivity, but on the other hand, they are susceptible to stress. Galangal rhizome (Kaempferia galanga) is a medicinal plant containing immunomodulatory compounds that play a role in enhancing and regulating the body's immune system. This study aimed to determine the potential of kencur rhizome on broiler chicken performance. The research design used was a Completely Randomized Design (CRD) with five treatments and five replications each. The treatments consisted of: KN (plain drinking water), KP (commercial vitamins), P1 (galangal rhizome 20 g/L), P2 (galangal rhizome 50 g/L), and P3 (galangal rhizome 80 g/L). Twenty-five one-day-old Ross 308 broilers were reared for 30 days. Parameters observed included water and feed intake, absolute body weight, relative growth rate, and morphological condition. Data were analyzed using ANOVA, followed by Duncan’s multiple range test at a 5% significance level. The results indicated that kencur supplementation significantly (p<0.05) affected water intake, absolute body weight, and relative growth rate. The P3 treatment (80 g/L) yielded the most favorable outcomes in growth and morphology. These findings suggest that galangal rhizome has potential as an immunomodulatory agent to enhance broiler performance